Letter from Conrad William Faber to James Curtis Booth, April 19, 1853 - Faber, Conrad William (1853)
Discussion of a variety of business matters.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Assaying; Metals--Refining